2004
DOI: 10.1128/aem.70.4.2052-2060.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Bacterial Community of Maple Sap by Using Amplified Ribosomal DNA (rDNA) Restriction Analysis and rDNA Sequencing

Abstract: The bacterial community of maple sap was characterized by analysis of samples obtained at the taphole of maple trees for the 2001 and 2002 seasons. Among the 190 bacterial isolates, 32 groups were formed according to the similarity of the banding patterns obtained by amplified ribosomal DNA restriction analysis (ARDRA). A subset of representative isolates for each ARDRA group was identified by 16S rRNA gene fragment sequencing. Results showed a wide variety of organisms, with 22 different genera encountered. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 25 publications
7
50
0
6
Order By: Relevance
“…Minimum cells of putative clones were used as templates in reaction mixtures during the re-amplification procedure. PCR products of positive clones were subjected to amplified ribosomal DNA restriction analysis (ARDRA) (Lagacé et al 2004) with HaeIII and HhaI (TaKaRa). Clones with identical ARDRA profiles were classified into one operational taxonomic unit (OTU).…”
Section: Standard Curve Of Real-time Pcrmentioning
confidence: 99%
“…Minimum cells of putative clones were used as templates in reaction mixtures during the re-amplification procedure. PCR products of positive clones were subjected to amplified ribosomal DNA restriction analysis (ARDRA) (Lagacé et al 2004) with HaeIII and HhaI (TaKaRa). Clones with identical ARDRA profiles were classified into one operational taxonomic unit (OTU).…”
Section: Standard Curve Of Real-time Pcrmentioning
confidence: 99%
“…Then, 200 clones in each clone library were obtained to select positive clones through PCR with the sets of vector-specific primers T7/SP6. PCR products of positive clones were subjected to amplified ribosomal DNA restriction analysis (ARDRA) with HinfI and HaeIII (Fermentas, Lithuania) [20].…”
Section: Construction Of 16s Rrna Gene Librariesmentioning
confidence: 99%
“…Lagace et al (2004) identified the bacterial community of maple trees. A wide variety of the organisms were detected from different groups.…”
Section: Amplified Ribosomal Dna Restriction Analysis (Ardra)mentioning
confidence: 99%